2015
DOI: 10.1080/08873267.2015.1047934
|View full text |Cite
|
Sign up to set email alerts
|

Singing your troubles away: The experience of singing from a psychological standpoint—Contributions from a heuristic research.

Abstract: Singing is a complex, multifaceted activity and a multidisciplinary area of research. Although it is a ubiquitous human phenomenon, its psychological aspects are yet to be fully understood. This article presents a brief overview of the latest psychological studies on singing, with the aims of contributing to describing the subjective experience of singing, based on first-person accounts and on the researcher's self-discovery process. Results are presented of a qualitative research study where 6 in-depth interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 61 publications
0
5
0
1
Order By: Relevance
“…Referred to as, “communicative musicality” (Trevarthen, 1999/2000) and “affective attunement” (Stern, 1985), parent–infant interactions that involve connecting and responding in a melodic fashion to each other confer positive effects on infant development (e.g., Custodero, 2006). Specifically, parents use lullabies and play songs to comfort, convey cultural values, teach, support family routines (Addessi, 2009; Custodero, Britto, & Xin, 2002; Ilari, 2005) and support emotion regulation in their young children (Creighton, Atherton & Kitamura, 2013).…”
Section: The Intergenerational Transmission Of Music Within Parent–inmentioning
confidence: 99%
See 1 more Smart Citation
“…Referred to as, “communicative musicality” (Trevarthen, 1999/2000) and “affective attunement” (Stern, 1985), parent–infant interactions that involve connecting and responding in a melodic fashion to each other confer positive effects on infant development (e.g., Custodero, 2006). Specifically, parents use lullabies and play songs to comfort, convey cultural values, teach, support family routines (Addessi, 2009; Custodero, Britto, & Xin, 2002; Ilari, 2005) and support emotion regulation in their young children (Creighton, Atherton & Kitamura, 2013).…”
Section: The Intergenerational Transmission Of Music Within Parent–inmentioning
confidence: 99%
“…Music confers positive physiological effects on newborn infants (Olischar, Shoemark, Holton, Weninger, & Hunt, 2011) and can reduce adults’ physiological stress response (Zimmerman, Pierson, & Marker, 1988). For instance, in a recent study of healthy mothers and infants (Creighton et al, 2013), mothers described feeling calm when singing to their children and they reported a sense of affirmation and increased focus when they could regulate their infant’s emotions through song.…”
Section: Musical Parenting and Contexts Of Riskmentioning
confidence: 99%
“…Brisola and Cury (2015), in their qualitative study of the singing experience, found that singing enhances the integration of one's cognitive, physical, social, cultural, and emotional well‐being (Brisola & Cury, 2015, p. 403). Participants reported that singing provided a deeper sense of consciousness, self‐value, self‐esteem, and stronger self‐awareness (Brisola & Cury, 2015, p. 402).…”
Section: Educational Factors Of Self‐awarenessmentioning
confidence: 99%
“…Brisola and Cury (2015), in their qualitative study of the singing experience, found that singing enhances the integration of one's cognitive, physical, social, cultural, and emotional well‐being (Brisola & Cury, 2015, p. 403). Participants reported that singing provided a deeper sense of consciousness, self‐value, self‐esteem, and stronger self‐awareness (Brisola & Cury, 2015, p. 402). Saunders et al (2007), in their qualitative study of the impact of an experiential mind–body skills course, found that it helped medical students achieve self‐awareness, self‐reflection, and self‐care (Saunders et al, 2007, p. 778).…”
Section: Educational Factors Of Self‐awarenessmentioning
confidence: 99%
“…Saúde mental materna tornou-se uma área de preocupação crescente para pesquisadores, clínicos e gestores de políticas públicas, já que há evidências de que as consequências de problemas emocionais de mães no período perinatal não estão limitadas ao sofrimento que as aflige, mas estendem-se à qualidade do relacionamento conjugal, ao relacionamento mãe-bebê e ao desenvolvimento da criança (Zelkowitz & Papageorgiou, 2012, p. 205, tradução nossa). Apesar de esses autores se preocuparem primordialmente com a ansiedade e depressão maternas, acreditamos que sua afirmação é igualmente verdadeira em se tratando de saúde mental (em oposição à doença); e, ousamos acrescentar, que a saúde mental da mulher também repercute no relacionamento com seu parceiro e filho(a). Se cantar já foi identificado por pesquisadores como um meio de promover saúde mental (Brisola & Cury, 2015), então deve ser mais bem compreendido e explorado.…”
Section: Introductionunclassified